Responses of grassland birds to patch-burn grazing in the Flint Hills of Kansas - Erickson, Amy Nicole (Kansas State University, 2017)
Grassland birds are declining throughout their native range. The Flint Hills of eastern Kansas and Oklahoma contain large tracts of tallgrass prairie, but intensification of agricultural practices may be contributing to ongoing population declines. Common rangeland management practices include annual burning coupled with heavy grazing by cattle. This system, known as intensive early stocking and burning, promotes homogeneous utilization of forage by cattle but may not provide habitat for some grassland bird species. Patch-burn grazing is an alternative management system that aims to restore heterogeneity on rangelands by recreating the fire-grazing interaction that would have historically occurred throughout the Great Plains. From 2011-2013, we examined responses of grassland birds to traditional rangeland management and patch-burn grazing by conducting vegetation surveys, line transect surveys, and nest monitoring on privately-owned pastures in Chase County and Greenwood County, Kansas. Vegetative heterogeneity was higher on patch-burned pastures, with unburned patches having higher visual obstruction and less bare ground. Densities of grassland birds differed by species and among habitat strata. Unburned patches on patch-burned pastures were associated with increased densities of Dickcissels (Spiza americana), Eastern Meadowlarks (Sturnella magna) and Grasshopper Sparrows (Ammodramus savannarum). Henslow’s Sparrows (A. henslowii) were only detected on patch-burned pastures. Nest survival of grassland songbirds was similar among management systems but varied by year. Probability of nest parasitism by Brown-headed Cowbirds (Molothrus ater) varied among years and between treatments for Dickcissels and Grasshopper Sparrows, with overall lower rates on burned areas and during drought years. For Dickcissels and Grasshopper Sparrows, there was a significant reduction in host clutch size between parasitized versus unparasitized nests. Overall, nest survival of grassland songbirds in managed rangelands was low. Patch-burn grazing improved rangeland conditions and provided habitat for more species of birds, but did not increase nest survival. Drought conditions in 2012 and 2013 may have influenced the results of this study, as many landowners were unable to burn as planned. Further study is needed to determine underlying factors driving variation in nest success and parasitism rates for grassland birds, particularly on private lands which make up the vast majority of remnant tallgrass prairies.
Keywords: Patch-burn grazing; Tallgrass prairie; Rangeland management; Nest survival; Grassland songbirds; Cowbird parasitism